The Role of Spinal Instability in Treating Unstable Infected Fractures - Shahid Husssin, Mohsin Ali Khan, Tauseef Raza, Muhammad Muneer Haider, Junaid Javaid, Akkad Rafiq, Yousaf Sulaiman Khan, Mian Iftikhar Ul Haq (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Unstable infected fractures of the spine present a complex challenge in orthopedic and spinal surgery. The management of these fractures requires a comprehensive approach to control infection, achieve fracture healing, and maintain spinal stability. Objective: To investigate the impact of spinal instability on infection resolution, fracture healing, and functional recovery in patients with unstable infected fractures. Methods: This prospective cohort study was conducted at KMU Institute of Medical Sciences, Kohat during June 2022 to January 2023. The study involved 55 patients with unstable infected fractures. Patients aged >18 years, diagnosed with unstable fractures involving infection, and with evidence of spinal involvement based on clinical and radiological assessments were included in the study. Results: 87.3% infection resolution rate, with 90.9% of patients achieving spinal stability postoperatively. The overall fracture healing rate was 90.9%, with a nonunion rate of 9.1%. Functional recovery, as measured by ODI scores, improved significantly, with a mean reduction in ODI scores from 38.5 preoperatively to 14.2 postoperatively. Patients who achieved spinal stability and infection resolution showed greater improvements in functional outcomes. However, 18.2% of patients experienced complications, including persistent infection, hardware failure, and nonunion. Conclusion: It is concluded that spinal stability plays a critical role in the successful treatment of unstable infected fractures. Effective infection control, fracture healing, and maintaining spinal stability are essential for achieving optimal functional recovery. Keywords: Patients, Management, Non-union, Orthopedic, Instability